2018
DOI: 10.1002/cpt.1197
|View full text |Cite
|
Sign up to set email alerts
|

The KHENERGY Study: Safety and Efficacy of KH176 in Mitochondrial m.3243A>G Spectrum Disorders

Abstract: KH176 is a potent intracellular reduction-oxidation-modulating compound developed to treat mitochondrial disease. We studied tolerability, safety, pharmacokinetics, pharmacodynamics, and efficacy of twice daily oral 100 mg KH176 for 28 days in a double-blind, randomized, placebo-controlled, two-way crossover phase IIA study in 18 adult m.3243A>G patients without cardiovascular involvement. Efficacy parameters included clinical and functional outcome measures and biomarkers. The trial was registered within Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 30 publications
(66 reference statements)
0
42
0
1
Order By: Relevance
“…www.nature.com/scientificreports/ Redox modulating compounds KH176 and KH176m partially reverses neuronal deficits in PRKN mutant DA neurons. In order to evaluate if the driving mechanism in PRKN mutant DA neurons is the loss of energy production by the mitochondria or the dramatically increased mitochondrial ROS production, we treated the end stage day 27 neurons with the known potent intracellular redox-modulating agents KH176 and KH176m 35 currently in clinical trials in mitochondrial patients with m.3243A>G spectrum disorders 36 . KH176 and its quinone metabolite KH176m were identified from a screen in fibroblasts from patients with primary mitochondrial diseases.…”
Section: Resultsmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Redox modulating compounds KH176 and KH176m partially reverses neuronal deficits in PRKN mutant DA neurons. In order to evaluate if the driving mechanism in PRKN mutant DA neurons is the loss of energy production by the mitochondria or the dramatically increased mitochondrial ROS production, we treated the end stage day 27 neurons with the known potent intracellular redox-modulating agents KH176 and KH176m 35 currently in clinical trials in mitochondrial patients with m.3243A>G spectrum disorders 36 . KH176 and its quinone metabolite KH176m were identified from a screen in fibroblasts from patients with primary mitochondrial diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Sonlicromanol (KH176; IUPAC chemical name (S)-6-hydroxy-2,5,7,8-tetramethyl-N-((R)-piperidin-3yl)chroman-2-carboxamide hydrochloride) is a clinical trial stage drug compound (phase 1 completed, phase 2a completed, phase 2b ongoing) (Koene et al, 2017;Beyrath et al, 2018;Janssen et al, 2019) with a triple mode of action (radical trapping, ferroptosis inhibition by inhibiting lipid peroxidation, anti-inflammatory inhibiting mPGES-1). Important in this context is that both the parent compound (sonlicromanol) and its metabolite (KH176m) are both active and, in humans, ~50% of the parent compound is converted to the active metabolite KH176m (Koene et al, 2017;Janssen et al, 2019).…”
Section: Sonlicromanol: a Clinical Trial Stage Drug Compound Selectivmentioning
confidence: 99%
“…We report that sonlicromanol, a compound targeting mitochondrial function, can improve both neuronal network function as well as changes in gene expression, representing mitochondrial respiration and synaptic function. Sonlicromanol has not yet been tested in a large-scale clinical trial, but the phase II clinical trial has already shown improvements in mood and alertness, often found in patients suffering from m.3243A>G related-and other mitochondrial diseases (Janssen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%